British monetary policy and the balance of payments, 1951-1957 - Kenen, Peter B. (Cambridge, Mass., Harvard University Press, 1960)
This essay began as a study of the United Kingdom's balance-of-payments difficulties in 1945-1955. It survey her domestic economic policies, especially monetary policies, in the light of her balance-of-payments position. It also appraises the Bank's recent efforts to control the supply of credit.
"The greater part of this essay was submitted to Harvard University as a doctoral dissertation in 1957."
Bibliography: p. [299]-313.
usc 16/06/17
Loans
Keywords: Currency question; Balance of payments; Monetary policy - British